ENHANCEMENT OF VOCABULARY THROUGH BILINGUAL DICTIONARIES USING NLP TECHNIQUES IN A TBLT-BASED ELT CLASSROOM - Abdul Ghafoor; Lubna Shahzadi; Rahat Anees; Noureen Tahir; Afshan (International Journal of Contemporary Issues in Social Sciences, 2024)
Pakistan remains one of the few nations where traditional methods for teaching English vocabulary persist, despite growing criticism for their outdated approach. This study evaluates the effectiveness of integrating Neuro-Linguistic Programming (NLP) techniques with Task-Based Language Teaching (TBLT) to enhance vocabulary acquisition in ESL classrooms, focusing on 9th-grade students in public schools in Okara, Punjab. Using a mixed-method approach, the study employed tests and SPSS for data analysis, with T-TESTs validating the findings. Results indicate that students exposed to NLP and TBLT techniques demonstrated significant improvements in vocabulary acquisition compared to those taught through conventional methods. These insights underscore the potential of modernized ESL strategies in boosting language proficiency, offering valuable guidance for educators, administrators, and policymakers in Pakistan.